Inhibition of Liquid-Liquid Phase Separation for Breaking the Solubility Barrier of Amorphous Solid Dispersions to Improve Oral Absorption of Naftopidil - Masafumi Fukiage; Kyosuke Suzuki; Maki Matsuda; Yohei Nishida; Michinori Oikawa; Takuya Fujita; Kohsaku Kawakami (MDPI AG, 2022)
Amorphous solid dispersion (ASD) is one of the most promising technologies for improving the oral absorption of poorly soluble compounds. In this study, naftopidil (NFT) ASDs were prepared using vinylpyrrolidone-vinyl acetate copolymer (PVPVA), hydroxypropyl methylcellulose acetate succinate (HPMCAS), and poly(methacrylic acid-co-methyl methacrylate) L100-55 (Eudragit) to improve the dissolution and oral absorption behaviors of NFT. During the dissolution process of ASD, liquid-liquid phase separation (LLPS) may occur when certain requirements are met for providing a maximum quasi-stable concentration achievable by amorphization. The occurrence of LLPS was confirmed in the presence of PVPVA and HPMCAS; however, Eudragit inhibited LLPS owing to its molecular interaction with NFT. Although the dissolution behavior of the Eudragit ASD was found to be markedly poorer than that of other ASDs, it offered the best oral absorption in rats. The findings of the current study highlight the possibility for improving the oral absorption of poorly soluble drugs by this ASD, which should be eliminated from candidate formulations based on the conventional in vitro tests.